Financial management in university professors and artificial intelligence as a tool for economic improvement - Antonio, Manco Chávez José; Rojas, Daniel Enrique Terrones; Luis, Bringas-Salvador Jorge; Cristina, Aranda Dextre Carmen; Josan, Carlos Aten Antonio Castro (International Journal of Innovative Research and Scientific Studies, 2025)
In today’s era of rapid technological advancement, everything changes transcendentally due to informatics in the development of AI. This is a basic non-experimental research, with a transactional or correlational design, descriptive, with a quantitative approach, generally using statistical analysis such as Spearman’s Rho correlation coefficient. The instruments were validated and passed the process of expert judgment intervention using Cronbach’s alpha statistic; the reliability coefficient for the first variable, Personal Finance, was 0.836, and for the second variable, Artificial Intelligence as a tool for economic improvement, the alpha was 0.986. Results revealed a weak positive correlation (Spearman’s Rho=0.222) between the personal finances of university professors and the perception of artificial intelligence as a tool for economic improvement, based on a survey of 46 university professors. However, the level of statistical significance (p=0.138) exceeds the standard threshold of 0.05, indicating that the relationship is not statistically significant. This may be attributed to limited familiarity or usage of AI tools in the personal financial practices of the surveyed educators. In conclusion, AI offers great potential to positively influence the personal finances of university professors by providing tools that simplify and optimize financial management. Although its direct impact may currently be limited, the advancement of these technologies promises to facilitate more informed and effective financial decisions.